GRAMMARLY AS A MEDIUM TO IMPROVE LEARNERS’ ENGLISH GRAMMAR IN ACADEMIC WRITING - Dasilva, Yudha Anfantri; Atmowardoyo, Haryanto; Muhayyang, Maemuna (Universitas Negeri Makassar, 2024)
This study examines the impact of utilizing Grammarly as a medium to increase learners' English grammar skills in academic writing. This research employed a writing test with pre-test and post-test. It focuses on 3rd-semester students at Universitas Negeri Makassar who have never used Grammarly. The grammar skills assessed were verb tense, word choice, subject-verb agreement, punctuation, and spelling. The findings indicated a significant improvement in learners' grammar scores following the treatment. The mean pre-test score was 73.17, while the mean post-test score climbed to 83. Furthermore, the data showed a significance value of.003, which is less than 0.05, indicating a statistically significant difference between pre-test and post-test findings. These findings suggest that Grammarly is an effective writing tool for increasing grammatical accuracy in academic writing.